Building a Natural Hazard Insurance System (NHIS): The Long-lasting Italian Case - Fabrizio Terenzio Gizzi (MDPI AG, 2021)
The worrying growth of extreme natural events and their socioeconomic impact over time is increasingly fuelling the debate on how to manage disasters in view of developing resilient and sustainable societies. One possible financial tool may be represented by insurance against natural hazards, such as earthquakes, floods, and landslides. From this perspective, the current article considers legislative attempts to build a Natural Hazard Insurance System (NHIS) in Italy. The (never promulgated) bills proposed over a time span of about 30 years were analysed by: (a) A text-mining technique, considering the extraction of relevant data for the research; (b) the careful reading of the texts and their cross-correlated critical analysis. Approximately forty bills have been proposed since the 1980s and they mainly concern the proposal of an NHIS based on a certain degree of compulsoriness (the voluntary system is contemplated only on a subordinate basis). Two possible main hurdles to the promulgation of such laws were inferred: the insurance scheme to be adopted and the issue of illegal buildings. Furthermore, the item of natural hazard risk perception was a factor not adequately considered by the bills. Based on the critical scrutiny of the bills and taking advantage of international experiences, the establishment of a voluntary national scheme managed by a public authority with specific competences on NHIS is proposed.